2002
DOI: 10.1017/s0790966700006959
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of forensic and general psychiatric services in Ireland: learning the lessons or repeating the mistakes?

Abstract: Objective:General psychiatric bed numbers in Ireland have reduced markedly in recent decades. In other jurisdictions such reductions have been accompanied by increases in the prevalence rates of severe mental illness among prisoners. We examined variations in per capita provision of local psychiatric beds and community residential places in Ireland for associations with forensic psychiatric service utilisation.Method:All admissions via the courts and prisons to the national forensic psychiatry service during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The high ARR of being a non-abusing forensic patient among Iranian men and Eastern European females is related to the high ARR of becoming a forensic patient among these two groups. It is often said that the increasing number of schizophrenic offenders is related to an increasing substance abuse among schizophrenic patients (17), but in accordance with other studies (18,19), our findings clearly indicate that reasons other than substance abuse, for instance, the insufficient treatment of schizophrenic patients in the era of deinstitutionalization (20,21), are the main explanations for the increasing number of schizophrenic forensic patients seen in many countries (22,23).…”
Section: Diagnosessupporting
confidence: 91%
“…The high ARR of being a non-abusing forensic patient among Iranian men and Eastern European females is related to the high ARR of becoming a forensic patient among these two groups. It is often said that the increasing number of schizophrenic offenders is related to an increasing substance abuse among schizophrenic patients (17), but in accordance with other studies (18,19), our findings clearly indicate that reasons other than substance abuse, for instance, the insufficient treatment of schizophrenic patients in the era of deinstitutionalization (20,21), are the main explanations for the increasing number of schizophrenic forensic patients seen in many countries (22,23).…”
Section: Diagnosessupporting
confidence: 91%
“…There is already strong evidence that mental health services in Ireland are inequitably distributed, with particular deficiencies in areas of greatest need [4,5]. Our findings indicate that the implementation of the Mental Health Act …”
Section: Discussionmentioning
confidence: 60%
“…People in areas suffering from high levels of social deprivation tend to have the highest rates of mental health problems and hence such areas have the greatest need for clinical resources and services. However, several studies (O'Neill et al, 2002;O'Keane et al, 2003;O'Keane et al, 2005) have found that it is the areas that are most in need of resources that are under-resourced. A Vision for Change recommended that extra funding be provided for areas that exhibit social and economic disadvantage with associated high prevalence of mental health problems.…”
Section: Figure 1: Mental Health Expenditure As Percentage Of Total Hmentioning
confidence: 99%